Wars in colour. Critical perspectives on digital colourisation in historical documentaries. - Simor, Kamilla (Visual Studies, 2025)
The article analyses the phenomenon created by colouring black and white archival footage in Revolution in Colour (Martin Dwan, 2016) and Warsaw Uprising (Powstanie Warszawskie, Jan Komasa, 2014) and focuses on how the contemporary cultural and media environment affects our perceptual mechanisms and makes the colourisation of archival black and white footage attractive. At the beginning of the paper, I briefly review the ontology of the digital image and concentrate on the way in which the archival footage is changed by being converted from analogue to digital. In addition, I focus on the possible social causes of digital colourisation and the visual consequences of adding colour to archival footage, emphasising the problem of spatiality, floating layers and reduction of temporal distance. Subsequently, I analyse different visual effects generated by the added colours in more detail in the case of the Irish film, along with a typology specifically constructed for this purpose, and with the description of the operations of immediacy and hypermediacy for coloured material. In the final subsection, I examine the phenomenological consequences of 'over-restoration' in the case of the Polish film and how the creators erased the traces of time. In this comparative analysis of the two films, my aim is to explore the differences between the two processes of digitisation and colourisation of archival footage.